The design and development of a proposed digital management solution for the UP School of Library and Information Studies - Lowe, Frances Elaine L. (2012)
The UP School of Library and Information Studies currently holds 1,500 theses and dissertations, photographs and newsletter, and forms. Some of the materials are difficult to access because of library or office limitations. The researcher intended to increase access and usage of these materials by developing a portal that encompasses the digitized materials. This study aimed to develop an online digital repository that shall contain four main modules for the UP SLIS materials.